PEMBUATAN ABON DAGING SAPI HYGIENIS DI KELURAHAN DARMO KOTA SURABAYA JAWA TIMUR - samsul huda; siti naviah (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Shredded is a processed product from beef, the process of making it simple through the initial stages is the meat is shredded and then cooked until it becomes shredded. This effort can be done simply with various creations, the problem is quality (hygienic) and management. The aim of the activity is to provide alternative solutions to some of the problems faced by producers in order to develop and be able to compete with other major snack industries and the availability of a sustainable skilled workforce. The location of the service was determined purposively in the darmo / Wonokromo sub-district of Surabaya as the place for the abon business partners and the local maternal labor. The results of this dedication concluded that at the production stage that needs to be considered is the quality of raw materials, because it affects the quality of the abon final product, in the production of large quantities required shredder machine technology. In return, management capital is needed for 2 months, with the added value of shredded production of Rp. 73,333.33 / kg